Rubber particles from four different species, examined by transmission electron microscopy and electron-paramagnetic-resonance spin labeling, are found to consist of a homogeneous rubber core enclosed by a contiguous,monolayer biomembrane - Cornish K; Windle J J; Wood D F (Planter, 1999)
The physical characteristics of rubber particles from the four rubber (cis-1, 4-polyisoprene) producing species Euphorbia lactiflua, Ficus elastica, Hevea brasiliensis and Parthenium argentatum were investigated using transmission electron microscopy (TEM) and electron-paramagnetic-resonance (EPR) spin labelling spectroscopy. Transmission electron microscopy showed the rubber particles to be composed of a spherical, homogeneous, core of rubber enclosed by a contiguous, electron-dense, single-track surface layer. The biochemical composition of the surface layer and its single-track TEM suggested that a monolayer biomembrane was the surface structure most compatible with the hydrophobic rubber core. The EPR spectra for a series of positional isomers of doxyl stearic acid, used to label the surface layer of the rubber particles, exhibited flexibility gradients and evidence for lipid-protein interactions for all four rubber particle types, which is consistent with a biomembrane-like surface. The EPR spectra confirmed that the surface biomembrane is a monolayer. Thus, rubber particles appear similar to oil bodies in their basic architecture. The EPR spectra also provided information on protein location and degree of biomembrane penetration that correlated with the known properties of the rubber-particle-bound proteins. The monolayer biomembranes serves as an interface between the hydrophobic rubber interior and the aqueous cytosol and prevents aggregation on the particles. An unexpected observation for the probes in pure polyisoprene was evidence of an intrinsic flexibility gradient associated with the stearic acid molecule itself.
Source Year: 2000
Keywords: Rubber particles; Transmission electron microscopy